Maud's line - Verble, Margaret (Houghton Mifflin Harcourt, 2015)
"Eastern Oklahoma, 1928. Eighteen-year-old Maud Nail lives with her rogue father and sensitive brother on one of the allotments parceled out by the U.S. government to the Cherokees when their land was confiscated for Oklahoma's statehood. Maud's days are filled with hard work and simple pleasures, but often marked by violence and tragedy, a fact that she accepts with determined practicality. Her prospects for a better life are slim, but when a newcomer with good looks and books rides down her section line, she takes notice"--Dust jacket flap.